Social Media Activation Strategy pada Produk Olahan Kelapa Kopyor “Kosudu” - Febriani, Alifia; Rochdiani, Dini; Rachmawati, Erna; Djuwendah, Endah (Universitas Galuh, 2024)
Coconut is a prospective plantation commodity. Many coconuts are further processed into various processed products, one of which is frozen coconut kopyor. This research aims to determine the implementation of brand activation and determine which social media activation strategy to be implemented in